Value of Magnetic Resonance Imaging and Audiology in the Emergency Department in Differential Diagnosis of Peripheral and Central Vertigo. - Özakin, Engin; Coskun, Figen; Saraç, Sarp; Oguz, Kader Karli; Bozkurt, Sebnem (Turkiye Klinikleri Journal of Medical Sciences, 2012)
ABS TRACT Ob jec ti ve: Ver ti go is a com mon comp la int in the emer gency ro om. Ver ti go can be central or pe rip he ral in ori gin and it is im por tant for an emer gency physi ci an to ma ke a cor rect dif fe - ren ti al di ag no sis. The pur po se of our study was to emp ha si ze the ro le of cra ni al mag ne tic re so nan ce ima ging (MRI) and au di o lo gi cal tests in dif fe ren ti al di ag no sis of pa ti ents who pre sent with ver ti go to the emer gency ro om. Ma te ri al and Met hods: Fifty pa ti ents (31 fe ma le, 19 ma le, me an age 50.84 ye ars) with ver ti go who we re ad mit ted to the Ha cet te pe Uni ver sity Fa culty of Me di ci ne Emergency Ro om (ER) bet we en 01.10.2004 and 31.01.2005 we re inc lu ded in the study. Physi cal and ne - u ro lo gi cal exa mi na ti ons of all pa ti ents we re per for med by se ni or re si dents and all pa ti ents we re eva lu a ted by Ear No se Thro at spe ci a lists. Au di o lo gic and ves ti bu lar tests and MRI with 3T (Tes la) mag ne tic fi eld po wer we re per for med in all pa ti ents. Re sults: Among 29 pa ti ents with nor mal ne - u ro lo gi cal exa mi na ti on, only 3 (10.3%) had le si ons on MRI. MRI scans re ve a led le si ons sug ges ting cen tral ver ti go eti o logy in six (18.2%) pa ti ents out of 33 with ab nor mal au di o lo gi cal test sug ges ting pe rip he ral ves ti bu lo pathy. Conc lu si on: In conc lu si on, in our pros pec ti ve study, ur gent cra ni al MRI tech ni qu e in pa ti ents pre sen ting to the emer gency ro om with ver ti go may re ve al sig ni fi cant fin dings re gar ding the dif fe ren ti al di ag no sis and con co mi tant pat ho lo gi es. Ho we ver, me ti cu lo us ne u ro lo gi - cal exa mi na ti on can exc lu de cen tral ver ti go in the ma jo rity of the pa ti ents.